The effect of ingested sulfite on visual evoked potentials, lipid peroxidation, and antioxidant status of brain in normal and sulfite oxidase-deficient aged rats. (July 2016) - Ozsoy, Ozlem; Aras, Sinem; Ozkan, Ayse; Parlak, Hande; Aslan, Mutay; Yargicoglu, Piraye; Agar, Aysel
Sulfite, commonly used as a preservative in foods, beverages, and pharmaceuticals, is a very reactive and potentially toxic molecule which is detoxified by sulfite oxidase (SOX). Changes induced by aging may be exacerbated by exogenous chemicals like sulfite. The aim of this study was to investigate the effects of ingested sulfite on visual evoked potentials (VEPs) and brain antioxidant statuses by measuring superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) activities. Brain lipid oxidation status was also determined via thiobarbituric acid reactive substances (TBARS) in normal- and SOX-deficient aged rats. Rats do not mimic the sulfite responses seen in humans because of their relatively high SOX activity level. Therefore this study used SOX-deficient rats since they are more appropriate models for studying sulfite toxicity. Forty male Wistar rats aged 24 months were randomly assigned to four groups: control (C), sulfite (S), SOX-deficient (D) and SOX-deficient + sulfite (DS). SOX deficiency was established by feeding rats with low molybdenum (Mo) diet and adding 200 ppm tungsten (W) to their drinking water. Sulfite in the form of sodium metabisulfite (25 mg kg −1 day −1 ) was given by gavage. Treatment continued for 6 weeks. At the end of the experimental period, flash VEPs were recorded. Hepatic SOX activity was measured to confirm SOX deficiency. SOX-deficient rats had an approximately 10-fold decrease in hepatic SOX activity compared with the normal rats. The activity of SOX in deficient rats was thus in the range of humans. There was no significant difference between control and treated groups in either latence or amplitude of VEP components. Brain SOD, CAT, and GPx activities and brain TBARS levels were similar in all experimental groups compared with the control group. Our results indicate that exogenous administration of sulfite does not affect VEP components and the antioxidant/oxidant status of aged rat brains.